Strategic Financial Decision in Uncertain Business Environment: Analisis pada PT IMC Pelita Logistik Tbk (PSSI) Periode 2023-2025 - Andi Mustika Amin (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the financial condition and formulate strategic financial decision strategies at PT IMC Pelita Logistik Tbk in facing uncertain business conditions. This study is motivated by the dynamics of the maritime logistics industry, which is heavily influenced by fluctuations in global commodity prices and pressures on operational efficiency. The research method used is a quantitative descriptive approach with financial ratio analysis covering liquidity (Current Ratio), solvency (Debt to Equity Ratio), and profitability (Net Profit Margin) based on financial report data for the 2023–2025 period. The results show that the company has excellent liquidity and solvency conditions, indicated by an increase in the current ratio from 4.07 to 7.17 and a decrease in the DER from 0.21 to 0.13. However, the company's profitability experienced a significant decline from 39.9% to 0.5%, indicating serious pressure on operational efficiency and profit-generating ability. Based on these findings, the recommended strategies are operational cost efficiency, fleet utilization optimization, and digital transformation through investment in a technology-based logistics management system. This study concludes that sound strategic financial decisions are essential to improving a company's profitability and long-term sustainability